Global ground-based tropospheric ozone measurements: reference data and individual site trends (2000–2022) from the TOAR-II/HEGIFTOM project - R. Van Malderen; A. M. Thompson; A. M. Thompson; D. E. Kollonige; D. E. Kollonige; R. M. Stauffer; H. G. J. Smit; E. Maillard Barras; C. Vigouroux; I. Petropavlovskikh; I. Petropavlovskikh; T. Leblanc; et al. (Atmospheric Chemistry and Physics)
Tropospheric ozone trends from models and satellites are found to diverge. Ground-based (GB) observations are used to reference models and satellites, but GB data themselves might display station biases and discontinuities. Reprocessing with uniform procedures, the TOAR-II working group Harmonization and Evaluation of Ground-based Instruments for Free-Tropospheric Ozone Measurements (HEGIFTOM) homogenized public data from five networks: ozonesondes, In-service Aircraft for a Global Observing System (IAGOS) profiles, solar absorption Fourier transform infrared (FTIR) spectrometer measurements, lidar observations, and Dobson Umkehr data. Amounts and uncertainties for total tropospheric ozone (TrOC; surface to 300 hPa), as well as free- and lower-tropospheric ozone, are calculated for each network. We report trends (2000 to 2022) for these segments using quantile regression (QR) and multiple linear regression (MLR) for 55 datasets, including six multi-instrument stations. The findings are that (1) median TrOC trends computed with QR and MLR trends are essentially the same; (2) pole-to-pole, across all longitudes, TrOC trends fall within +3 to −3 ppbv per decade, equivalent to (−4 % to +8 %) per decade depending on site; (3) the greatest fractional increases occur over most tropical and subtropical sites, with decreases at northern high latitudes, but these patterns are not uniform; (4) post-COVID trends are smaller than pre-COVID trends for Northern Hemisphere mid-latitude sites. In summary, this analysis conducted in the frame of TOAR-II/HEGIFTOM shows that high-quality, multi-instrument, harmonized data over a wide range of ground sites provide clear standard references for TOAR-II models and evolving tropospheric ozone satellite products for 2000–2022.